Probiotic jelly candies enriched with native Atlantic Forest fruits and Bacillus coagulans GBI-30 6086. (May 2020) - Miranda, Jéssica Soares; Costa, Beatriz Veltre; de Oliveira, Isabela Valente; de Lima, Diana Clara Nunes; Martins, Eliane Maurício Furtado; de Castro Leite Júnior, Bruno Ricardo; Almeida do Nascimento Benevenuto, Wellingta Cristina; Campelo de Queiroz, Isabela; Ribeiro da Silva, Roselir; Martins, Maurilio Lopes
Abstract: This research aimed to develop juçara and passion fruit flavored gelatin confections with Bacillus coagulans GBI-30 6086. The jelly candies were evaluated during 90 days of shelf life for the physico-chemical characteristics, antioxidant capacity, microbiological characteristics, probiotic viability, the resistance of the strain to the gastrointestinal tract (GIT) simulated in vitro as well as sensory acceptance. The candies maintained of physical chemical characteristics without modification over time ( P > 0.05) and they were safe for consumption according to Brazilian legislation. B. coagulans maintained counts greater than 6.4 Log CFU/g over 90 days. In the in vitro GIT test, there was 6.82 Log CFU/g in enteral phase II. Consuming of 30 g portion of the candies give about 7.82 Log CFU/g of the probiotic, promoting benefits to consumers. The elaborated candies presented excellent acceptability. The results suggest that the juçara and passion fruit jelly candies represent an excellent carrier of B. coagulans . The addition of juçara and passion fruit pulps is industrially viable as a substitute of artificial dyes, being a source of bioactive compounds and it has potential in the candies market due to the health benefits. Highlights: The juçara and passion fruit pulp acted like a natural additive, a source of flavor and colorant. The jelly candies present an excellent carrier of Bacillus coagulans GBI-30 6086. Portion of 30 g of candies offers approximately 7.82 Log CFU/g of the probiotic microorganism. The candies are sensory promising and they have a functional appeal. The product has a positive impact on the confectionery industry.